Implementasi Pelatihan Penanaman Jagung dalam Meningkatkan Kemandirian Kelompok Tani di Balai Penyuluhan Pertanian Kecamatan Pogalan Kabupaten Trenggalek - Nurcahyani, Aprilia Amanda; Artha, I Ketut Atmaja Johny (J+PLUS UNESA, 2024)
his training is part of community empowerment, training can be implemented and has a purpose. The aim of this research is to analyze theimplementation of corn planting training in increasing the independence of farmer groups. This research uses a qualitative approach with descriptive research type. The research subjects included field agricultural instructors, the head of the farmergroup and two members of the farmer group. Research location at the Agricultural Extension Center. Data collection techniques using in-depth interviews, participant observation and documentation. Data analysis in research is carried out by collecting data, condensing data, presenting data, and verifying. The validity of research data is credibility, researchers use two methods, namely member checking and triangulation, then dependability, confirmability, transferability. The results of this research showed that the implementation of corn planting training in increasing the independence of farmer groups went quite well, as demonstrated by using the planning, implementation and evaluation stages.